Effect of adding ribbond fibres on marginal adaptation in class II composite restorations in teeth with affected dentine - Mukesh Kumar Hasija, Dr; Babita Meena; Deepti Wadhwa; Vivek Aggarwal (Journal of Oral Biology and Craniofacial Research)
Objective: To evaluate the feasibility and effect on marginal adaptation in class II composite restoration reinforced with polyethylene fibres in teeth with affected dentine using scanning electron microscopy. Method and material: Class II cavities with dimension 1.5 +0 .25 pulpal depth and 4 ± 0.25 mm buccolingual width/.were prepared on proximal surfaces extracted human molars or premolar with affected/sound dentine on gingival margin. The etching priming and restorations were done in prepared samples as per manufacture directions. The samples were divided in 2 groups depending on use of ribbond inserts in composite restorative material. Samples were finished, stored in distilled water and then thermocycled manually and then sectioned longitudinally through the restorations. The marginal adaptation was evaluated using scanning electron microscope (SEM). Result: The result showed that there was a definite gap all along the interface between caries affected dentine and the composite material in both the groups. The bigger gap was present in group II compared to group I.